'Continuous abuse' or 'a unanimous blessing'? Reassessing the Conservative Party's stance on the 1951 Festival of Britain. Issue 4 (2nd October 2017) - Wilton, Iain
Abstract: The 1951 Festival of Britain has long been seen as both a key turning point in the country's post-war history and an event which was delivered, by Clement Attlee's Labour Government, in the face of formidable political (and media) opposition. This article considers the Festival's status as a pivotal moment in modern British history but focuses primarily on the Conservative Party's approach to the project. In doing so, its draws on previously neglected evidence to suggest that successive works on the subject have greatly exaggerated the extent to which the festivities were the subject of partisan campaigning and political contention.